1990
DOI: 10.1111/j.1464-410x.1990.tb14760.x
|View full text |Cite
|
Sign up to set email alerts
|

Silver Alloy Coated Catheters Reduce Catheter‐associated Bacteriuria

Abstract: The tendency of indwelling catheters to cause urinary tract infection was evaluated in a randomised clinical study of 223 patients. A Foley catheter coated with silver alloy on both inner and outer surfaces was used in 60 patients; 60 others received a Teflonised latex Foley's catheter and the remaining 103 patients were excluded because of antibiotic treatment, diabetes, etc. There was a statistically significant difference in the incidence of catheter-associated bacteriuria (greater than 10(5) organisms/ml) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(78 citation statements)
references
References 15 publications
0
77
0
1
Order By: Relevance
“…Silver is known to be antibacterial and nontoxic to mammalian tissue and has been used in various clinical settings, such as burn wounds and pressure ulcers. In the last 15 years, numerous randomized clinical trials and a meta-analysis in the general inpatient population have shown that SHCs reduce the incidence of catheter-associated nosocomial UTIs [16][17][18][19][20]. Prospective, randomized controlled trials involving silver alloy-coated catheters have demonstrated decreased nosocomial UTIs and the associated cost benefits in short-term inpatient settings.…”
Section: Introductionmentioning
confidence: 99%
“…Silver is known to be antibacterial and nontoxic to mammalian tissue and has been used in various clinical settings, such as burn wounds and pressure ulcers. In the last 15 years, numerous randomized clinical trials and a meta-analysis in the general inpatient population have shown that SHCs reduce the incidence of catheter-associated nosocomial UTIs [16][17][18][19][20]. Prospective, randomized controlled trials involving silver alloy-coated catheters have demonstrated decreased nosocomial UTIs and the associated cost benefits in short-term inpatient settings.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-two of the included studies were parallel group randomized controlled trials 13,[15][16][17][18][19][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and one was a cluster-randomized cross-over trial 35 comparing two or three types of indwelling urinary catheters. The 22 parallel group randomized controlled trials included 5,236 hospitalized adults (mean n=208, range n=27-1,309).…”
Section: Designmentioning
confidence: 99%
“… Several trials 13,19,21,23,25,26,[28][29][30]32,34,35 included both women and men catheterized for hemodynamic monitoring or post-operative drainage for a variety of diagnoses.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 More recently, the introduction of silver-coated Foley catheters lead to a statistically significant reduction of bacteriuria in patients who had undergone prolonged catheterization. [9][10][11][12][13] Moreover, the use of silver-coated central venous catheters in parenteral nutrition was shown to significantly decrease the rate of sepsis. 14,15 Recently, silver coating of stainless steel screws, implanted in sheep iliac bone and inoculated with Staphylococcus aureus, was found to be effective in reducing the number of colony-forming units when compared with uncoated screws.…”
Section: Introductionmentioning
confidence: 99%